MEDAN GAYA BERAT DAN MODEL GEODINAMIKA DI SEKITAR KEPULAUAN KAI DAN KEPULAUAN ARU, MALUKU - Budi Setyanta (Jurnal Geologi dan Sumberdaya Mineral, 2010)
A gravity measurement was done to study geodynamic model in Kai and Aru islands. Bouguer anomaly in Kai-Aru region can be separated into two groups namely, western part of anomaly group with slighth up and down sharp gradient and the eastern part of anomaly group which is slightly smooth. Both groups of anomaly range from -180 mgals to 200 mgals and is interpreted that the lithologies in that area are underlain by continental crust. A geodynamic hypothesis around Kai-Aru islads based on subsurface gravity model shows that the Kai islands are constructed by thrusting mechanism whereas the Aru islands are by drifting mechanism and followed by gravitational tectonic mechanism. Both mechanism are influenced by changing mechanism from compressional to extentional tectonic regime.Key words : Bouguer anomaly, tectonic mechanism, geodynamics, Maluku